Development of ultrasound‐assisted emulsification microextraction based on solidification of a floating organic droplet for determination of organochlorine pesticides in water samples. Issue 4 (11th January 2016) - Shu, Bin; Yang, Zhaoguang; Lee, Hsiaowan; Qiu, Bo; Li, Haipu
Abstract : An ultrasound‐assisted emulsification microextraction based on the solidification of a floating organic droplet followed by gas chromatography with electron capture detection was developed for the simultaneous determination of 13 organochlorine pesticides in water samples. In the proposed method, ultrasound was applied to achieve the emulsification without addition of any dispersive solvent. In consequence, the volume of extraction phase remained unaffected by the ion strength of aqueous phase and high extraction recoveries were obtained. It was also found that dilution of the floating phase with acetone was necessary for preventing peak splitting in chromatogram. Under optimal conditions, the proposed method provided good sensitivity (the detection limits of organochlorine pesticides ranged from 1.3 to 3.9 ng/L) and good repeatability of extraction (below 6.5%, n = 5). The recoveries in reservoir and river water samples were between 75.8% and 96.9%.